Hypoglicemic and Antioxidant Activity of Petiveria alliacea in Diabetic Rat Models - Vania Azalia Gunawan; Harlina Soetjipto; Arifa Mustika (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2020)
Introduction: Diabetes mellitus is a degenerative disease characterized by chronic hyperglycemia conditions in the body. Various complications of diabetes mellitus are caused by oxidative stress condition. Petiveria alliacea (P. alliacea) is a potential plant and easy to grow in hot regions. Leaf extracts of P. alliacea contain flavonoids and tannins which work as antidiabetic and antioxidant. In addition, other compounds found in P. alliacea leaf extracts like linoleic acid and allantoin show an increase in insulin secretion. Therefore, this study aimed to determine the antidiabetic activity of ethanolic extract of P. alliacea. Methods: We investigated the hypoglycemic and antioxidant effect of P. alliacea on STZ-induced diabetic rats. Rats were randomly divided into six groups named normal control, diabetes control, metformin (150 mg/kg/d), low dose of P. alliacea (90 mg/kg/d), intermediate dose (180 mg/kg/d), and high dose (360 mg/kg/d). Rats were orally given the treatment daily in the morning for fourteen days. At the end of the study, blood glucose level was measured and rats were sacrificed to measure blood malondialdehyde level.malondialdehydeResults: P. alliacea extract dose of 90 mg/kg and 360 mg/kg, and also metformin significantly decrease blood glucose levels. P. alliacea extract dose of 360 mg/kg was able to lower blood malondialdehyde level significantly which were not obtained on metformin. Conclusion: This finding suggests that ethanolic extract of P. alliacea possess antidiabetic effect at least on rats.